1984
DOI: 10.1061/(asce)0733-9399(1984)110:3(329)
|View full text |Cite
|
Sign up to set email alerts
|

Rate‐Type Concrete Creep Law with Reduced Time

Abstract: For creep analysis of large structural systems, the linear aging integral-type creep law needs to be converted to a rate-type form which consists of a system of first-order linear differential equations with age-dependent coefficients. The system may be visualized by the Kelvin chain model with agedependent elastic moduli and viscosities. In the existing formulation, the independent variable is actual time. It is shown that, by using as the independent variable a certain reduced time which increases with time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…At the same time, studies of fracture test data of concrete showed that strain-softening stress-strain relations are inevitable for de-SCribing the observed deviations from linear elastic fracture mechanics or from strength criteria, and for obtaining the correct structural size effect (12,31). Also, it has been found that the same strain-softening stressstrain relations yield correct deflections of reinforced concrete beams in the cracking stage (10), and explain the existing test data on the shear transmission across cracks with the associated dilatancy (8). Thus, the tensile strain softening-a property well-established experimentally (19,(21)(22)(23)25,26,31)-emerges as a fundamental property of concrete.…”
Section: Introductionmentioning
confidence: 58%
“…At the same time, studies of fracture test data of concrete showed that strain-softening stress-strain relations are inevitable for de-SCribing the observed deviations from linear elastic fracture mechanics or from strength criteria, and for obtaining the correct structural size effect (12,31). Also, it has been found that the same strain-softening stressstrain relations yield correct deflections of reinforced concrete beams in the cracking stage (10), and explain the existing test data on the shear transmission across cracks with the associated dilatancy (8). Thus, the tensile strain softening-a property well-established experimentally (19,(21)(22)(23)25,26,31)-emerges as a fundamental property of concrete.…”
Section: Introductionmentioning
confidence: 58%
“…This procedure is difficult, consuming in computational effort, and in essence only provides an approximation to the compliance function. Moreover, in many cases the use of differential type constitutive relations based on Kelvin or Maxwell chains violates basic thermodynamics laws, where the spring moduli and dashpot viscosities become negative (see Bazant and Chern, 1984). Hence, the integral-type constitutive relation, which is also applicable to any compliance function, is preferred and used here.…”
Section: Incremental Time-stepping Approachmentioning
confidence: 97%
“…The rate of creep of the concrete material approaches zero as time increases. Hence, when this method is applied for the buckling analysis of concrete structures, where creep causes a significant variation of the internal stresses in time or when the structure is gradually loaded, it may lead to erroneous results because of its inability to accurately asses the creep caused by loads that are applied at older ages [Bažant 1988;Gilbert 1988]. Therefore, a model that is able to account for these effects needs to be implemented in the creep buckling analysis of concrete domes.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of creep and shrinkage on the behaviour of concrete structures have been widely studied and reported [Bažant 1988;Gilbert 1988]. However, very little advanced research appears to have been reported on these effects in concrete shell structures, and in shallow concrete domes in particular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation